My social media for seniors - Miller, Michael 1958- (Que, 2016)
Interested in Pinterest? Want to link up with LinkedIn? You're interested in social media, but not sure exactly what to do-- or which media best suits your needs. Miller helps you identify your essential skill sets, and gives you tips on choosing and using social media safely and privately.
"AARP, real possibilities.". - Includes index. - Online resource; title from title page (Safari, viewed November 16, 2015)
Keywords: Computers and older people; Online social networks; Social media; Social Media; Ordinateurs et personnes âgées; Réseaux sociaux (Internet); Médias sociaux; social media